2004
DOI: 10.1104/pp.104.047043
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of Ribosomal Proteins to RNA in Maize Ribosomes by UV-B and Its Effects on Translation

Abstract: Ultraviolet-B (UV-B) photons can cause substantial cellular damage in biomolecules, as is well established for DNA. Because RNA has the same absorption spectrum for UV as DNA, we have investigated damage to this cellular constituent. In maize (Zea mays) leaves, UV-B radiation damages ribosomes by crosslinking cytosolic ribosomal proteins S14, L23a, and L32, and chloroplast ribosomal protein L29 to RNA. Ribosomal damage accumulated during a day of UV-B exposure correlated with a progressive decrease in new prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…5A; Supplemental Fig. S4), in agreement with results obtained in experiments with maize plants exposed under UV-B radiation (Casati and Walbot, 2004). rpl10C and rpl10B mutant plants did not show significant differences in protein synthesis under control and UV-B exposure conditions compared with wild-type plants (Fig.…”
Section: Participation Of Rpl10s In Translation Under Uv-b Lightsupporting
confidence: 80%
See 3 more Smart Citations
“…5A; Supplemental Fig. S4), in agreement with results obtained in experiments with maize plants exposed under UV-B radiation (Casati and Walbot, 2004). rpl10C and rpl10B mutant plants did not show significant differences in protein synthesis under control and UV-B exposure conditions compared with wild-type plants (Fig.…”
Section: Participation Of Rpl10s In Translation Under Uv-b Lightsupporting
confidence: 80%
“…In a previous work, we found that UV-B radiation induces ribosomal damage, which occurs via formation of cross-links between RNA and specific ribosomal proteins, resulting in a 50% reduction in protein synthesis (Casati and Walbot, 2004). To study the role of RPL10 isoforms in translation, and their participation in translation under UV-B stress, we performed in vivo labeling of leaf proteins with [ 35 S]Met in control plants (no UV-B) and after exposure under UV-B radiation for 4 h (4 h UV-B).…”
Section: Participation Of Rpl10s In Translation Under Uv-b Lightmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants, because of their sessile condition and their requirement of sunlight for photosynthesis, are inevitably exposed to UV-B radiation (290-315 nm), which causes direct damage to DNA, proteins, lipids, and RNA (Britt, 1996;Jansen et al, 1998;Gerhard et al, 1999;Casati and Walbot, 2004a). Thus, plants have not only developed mechanisms that filter or absorb UV-B to protect them against DNA damage (Mazza et al, 2000;Bieza and Lois, 2001) but also have different DNA repair systems to remove or tolerate DNA lesions (Hays, 2002;Bray and West, 2005;Kimura and Sakaguchi, 2006).…”
mentioning
confidence: 99%